2009
DOI: 10.14742/ajet.1153
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the m-learning research agenda for active, experiential learning: Four case studies

Abstract: <span>This article reports on an m-learning research agenda instituted at our university in order to explore how mobile technology can enhance active, experiential learning. Details of the implementation and results of four areas of m-learning are presented: mobile supported fieldwork, fostering interactivity in large lectures with mobile technology, using mobile devices to learn about mobile technology and, finally, podcasting. These directions are informed by a concern for achieving m-learning practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 27 publications
(20 reference statements)
1
43
0
8
Order By: Relevance
“…Kennedy, Judd, Churchward, Gray & Krause (2008), Oliver and Goerke (2007), and Dyson, Litchfield, Lawrence, Raban & Leijdekkers (2009) found that approximately 30% of students in Australian universities did not own an MP3 player or experienced difficulties when trying to download material (Oliver & Goerke 2007;Kennedy et al 2008;), and thus podcasts could be accessed only via a computer. There is also the risk that outdated and revised instructional material will be uploaded in a new format, rather than created for the new format to engage and motivate the students (Sharma & Kitchens, 2004;Corbeil & Valdes-Corbeil, 2007;Duncan-Howell & Lee, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kennedy, Judd, Churchward, Gray & Krause (2008), Oliver and Goerke (2007), and Dyson, Litchfield, Lawrence, Raban & Leijdekkers (2009) found that approximately 30% of students in Australian universities did not own an MP3 player or experienced difficulties when trying to download material (Oliver & Goerke 2007;Kennedy et al 2008;), and thus podcasts could be accessed only via a computer. There is also the risk that outdated and revised instructional material will be uploaded in a new format, rather than created for the new format to engage and motivate the students (Sharma & Kitchens, 2004;Corbeil & Valdes-Corbeil, 2007;Duncan-Howell & Lee, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To go to the next step, which is encouraging and enabling students to generate the podcasts (Chan et al, 2006;Dyson, Litchfield, Lawrence, Raban, & Leijdekkers, 2009), requires valuing student voice (Schmit, 2007). As Atkinson (2006) notes, "the emerging developmental and research direction seems to me to be learning through creating podcasts and similar, in contrast to learning from podcasts" (p. 2, emphasis in original).…”
Section: Educational Podcasting: Trends and Issuesmentioning
confidence: 99%
“…Some authors raise the possibility that podcasting can amount to little more than content "spoon feeding", especially when used for transmission purposes (French, 2006;Herrington & Herrington, 2007;Lum, 2006), leading to the accusation that podcasting may be contrary to experiential learning (Dyson et al, 2009;French, 2006). Most of these criticisms, however, relate to podcasts generated by staff for a student audience, since student-generated podcasts are rarely considered.…”
Section: Why Podcast?mentioning
confidence: 99%
“…In Dyson et al (2009), four case studies for embedding mLearning into conventional educational practices, namely: 1) mobile supported fieldwork, 2) interactive mLearning in large lectures, 3) using mobile technology to learn about mobile technology and 4) Podcasts of lecture summaries have been reported. These and other similar projects face several challenges.…”
Section: Mlearning and Study Modementioning
confidence: 99%